Does erythropoietin treatment of anaemia in chronic renal failure protect the heart? - Wanic-Kossowska, Maria (Przewodnik Lekarza/Guide for GPs, 2007)
Anaemia, due to lack of erythropoietin, is a serious complication in patients with chronic kidney disease (CKD). It is known that anaemia is an independent risk factor of mortality in over 60% of patients caused by cardiovascular complications in CKD. Erythropoietin treatment has a beneficial effect on the function and heart structure and prevents progressive development of cardiovascular complications in CKD patients.